Regulamentação de biossegurança de organismos geneticamente modificados : uma abordagem a partir da dinâmica da ciência - Borges, Bárbara Juliana Pinheiro (2018)
Numerous scientific research, testing, and analysis with genetically modified organisms (GMOs) and products are currently conducted to ensure their safety for development and commercialization. Considering evolution of biotechnology, new biotechnological tools have been developed. They even enable the promotion of undetectable genetic modifications. These procedures are carried out based on the observation of previously established biosafety standards. It turns out that the standards currently in force were elaborated under an old paradigm - in which there was less acknowledgment about risk. In this way, questions are raised regarding the adequacy of the scientific criteria used by the current regulation to the new biotechnological tools. Through the analysis of two contexts or regulated matters, namely, (i) biosafety of GM plant (genetically modified) through microRNA techniques; and (ii) mandatory labeling of GM foods, the present study has identified the need for legislation (lato sensu) to increasingly incorporate arguments based on science rather than on ideological elements. Otherwise, it may promote restriction for society's access to the benefits generated through investment in Science, Technology and Innovation in the area of Biotechnology. Contrasting the principles of precaution, history of safe use and familiarity with the guidelines of international institutions on GMO biosafety, the discussion goes further to question the adequacy of current regulations not only to GMOs generated through new tools but also by other techniques. Thus, biosafety regulation, whose rules outline activities involving GMOs and derivatives, as well as food labeling rules, demands dynamism and must go hand in hand with scientific advances. We concluded that updating the Biosafety Law will legitimize technical competence of the Brazilian National Biosafety Technical Commission (CTNBio) as a regulatory agency and reorientate the role of Brazilian National Biosafety Council (CNBS) in the risk analysis process.